University students' sense of belonging to the home town: the role of residential mobility
In the study of young people's relationships with residential contexts, it is important to consider the role of developmental tasks (e.g. identity construction, academic and professional choices, etc.) in influencing Place Identity and Sense of Community. Residential mobility may represent an adaptive strategy for modifying some aspects of one's identity and a contributing factor to the development of autonomy from the family. Limited attention has been devoted to the study of the ways young people deal with their attachments to old and new places within this process. This study involved 203 university students, attending a large university in the North of Portugal. The aim was to investigate Place Identity (PI) and Sense of Community (SoC) related to the home town, and differences according to residential condition (native vs. temporary resident) and year of attendance (I vs. IV). Among students who moved, the role of motives (forced vs. voluntary) and of residential choices after graduation on PI and SoC were assessed. Results indicated that, among students who moved for academic reasons, SoC and PI related to the home town were lower and decreased from the first to the fourth year. SoC was higher among students who experienced the relocation as a forced choice. Students who anticipated to return to their home town after graduation had higher SoC and PI.